Dampak Komunikasi Organisasi dan Stres Kerja terhadap Kinerja Karyawan - Rinaldi, R; Tarmedi, Eded; Sumiyati, Sumiyati (Universitas Pendidikan Indonesia, 2018)
The purpose of this paper is to understand organizational communication and work stress on employee performance. The method used is an explanatory survey, and a population of 32 respondents. The analysis technique used is multiple linear regression processed using SPSS 16.0, the questionnaire is used as a research instrument to collect data from respondents. Important employee performance by organizational communication but not significant and employee performance interests by positive and significant. Organizational communication and work stress are used to improve employee performance. This study was used to describe the influence of organizational communication, work stress on the performance of employees in production employees of PT. Indolakto. The object that becomes the unit of analysis in this study is employees of PT. Indolakto Jakarta. The independent variables in this study are organizational communication and work stress, and the dependent variable is employee performance